2018
DOI: 10.1007/s11356-018-1671-5
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and subcellular distribution of cadmium in tea plant (Camellia sinensis cv. “Shuchazao”)

Abstract: A hydroponic experiment was performed to investigate the Cd absorption and subcellular distribution in tea plant, Camellia sinensis. Increased Cd accumulation potential was observed in the tea plant in a Cd-enriched environment, but most of the Cd was absorbed by the roots of C. sinensis. The Cd in all the root fractions was mostly distributed in the soluble fraction, followed by the cell wall fraction. By contrast, the Cd was least distributed in the organelle fraction. The adsorption of Cd onto the C. sinens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Cd in cell walls represented only 11% of the metal content (Carrier et al, 2003). In tea seedlings, most of the Cd accumulated in roots, with about 12% to 30% in the cell walls, while cell wall represented 43.6-83.4% of the very low Cd content in leaves (Cao et al, 2018a). Cosio et al (2005) showed that 33-35% of Cd in the aerial parts of N. caerulescens is in the cell walls.…”
Section: B Storage In the Apoplastmentioning
confidence: 99%
See 1 more Smart Citation
“…Cd in cell walls represented only 11% of the metal content (Carrier et al, 2003). In tea seedlings, most of the Cd accumulated in roots, with about 12% to 30% in the cell walls, while cell wall represented 43.6-83.4% of the very low Cd content in leaves (Cao et al, 2018a). Cosio et al (2005) showed that 33-35% of Cd in the aerial parts of N. caerulescens is in the cell walls.…”
Section: B Storage In the Apoplastmentioning
confidence: 99%
“…It should be noted that in several of the above-cited works (Lozano-Rodriguez et al, 1997;Carrier et al, 2003;Cao et al, 2018a), as well as in others (e.g. (Fu et al, 2011;Wang et al, 2015a;Wang et al, 2015b), the method used to determine Cd (or other elements) in cell walls is questionable.…”
Section: B Storage In the Apoplastmentioning
confidence: 99%
“…Wang et al found that under low-concentration Cd stress, more than 50% of Cd is combined in the f1 of the root cells of pakchoi varieties Huajun2 and Hanlv, a large amount of Cd enters f3 under higher Cd stress, and the proportion of Cd in f1 is decreased [5]. Yang et al found that the Cd distribution in rice roots is f3 > f1 > f2, and with the increase in the Cd stress, the proportion of Cd in the soluble and cell wall fraction increases significantly [61], which is similar to that in Camellia sinensis L. [62] and Phytolacca americane L. [63]. This may be due to the fixation of Cd in the cell wall after saturation; Cd is transported to the vacuole, and combined with the organic acid, organic base and protein in the vacuole to form a compartmentalization of the vacuole, thereby reducing the distribution of Cd in the organelles [63].…”
Section: Root Cell Wall Might Play a Key Role In The CD Accumulationmentioning
confidence: 72%
“…More recently, Huang et al (2017b) described the protective role of Ca against Cdinduced toxicity in plants. In a similar study, Cao et al (2018) described how the homeostasis of Ca and Mg in Camellia sinensis after Cd treatment was affected at Cd concentrations between 1 and 15 mg/L, noting that the intracellular Ca content in leaves increased with increasing Cd stress, but was much less pronounced for Mg. As documented by Yang et al (2015), treating horseradish roots with Tb(III) resulted in Tb(III) accumulation in both the extracellular and intracellular spaces of the roots, accompanied by increasing intracellular Ca content as well. These various studies confirm that plant cells do respond to PTM stress with an increased concentration of intracellular Ca.…”
Section: Resultsmentioning
confidence: 98%